Nematodes associated with terrestrial slugs from canola fields and ornamental nurseries in South Africa - Pieterse, Annika; Malan, Antoinette P.; Kruitbos, Laura M.; Sirgel, Willem; Ross, Jenna L. (Zootaxa, 2017)
A survey of nematodes that use terrestrial slugs as definitive hosts, was conducted in canola fields and ornamental nurseries located in the Western Cape province of South Africa. A total of 3290 slugs were collected from 22 different sites. On the identification of the slugs, they were vivisected and examined for internal nematodes. After identifying the nematodes found, on the basis of their morphological characteristics, their identity was confirmed using molecular sequence data for the internal transcribed spacer (ITS-1, 5.8S, ITS-2), D2-D3 expansion segments of the large subunit (LSU or 28S) and small subunit (SSU or 18S) ribosomal DNA. Of the 22 sites investigated, 13 had nematodes present, with 8 % of the slugs being found to be infected with nematodes. Seven nematode species were confirmed, including Agfa flexilis, Angiostoma margaretae, Angiostoma sp. (SA1), Caenorhabditis elegans, mermithid sp. (SA1), Phasmarhabditis sp. (SA3) and Phasmarhabditis sp. (SA4). In addition, several Angiostoma spp. were also isolated, but could only be identified to genus level due to limited material. Of the seven confirmed species, four were previously undescribed. This is the first record of A. margaretae associating with Deroceras panormitanum, Deroceras reticulatum, Lehmannia valentiana and Oopelta polypunctata. Also, this is the first time that a mermithid has been found associating with molluscs in South Africa.